2022
DOI: 10.2196/29973
|View full text |Cite
|
Sign up to set email alerts
|

User-Centered Design of A Novel Risk Prediction Behavior Change Tool Augmented With an Artificial Intelligence Engine (MyDiabetesIQ): A Sociotechnical Systems Approach

Abstract: Background Diabetes and its complications account for 10% of annual health care spending in the United Kingdom. Digital health care interventions (DHIs) can provide scalable care, fostering diabetes self-management and reducing the risk of complications. Tailorability (providing personalized interventions) and usability are key to DHI engagement/effectiveness. User-centered design of DHIs (aligning features to end users’ needs) can generate more usable interventions, avoiding unintended consequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This may need to be considered when the platform is offered to people with chronic health conditions to increase their engagement and motivation to use features for recipes, meal planning, and creating web-based shopping lists. Apart from personalized recipe suggestions, using AI could improve engagement with such platforms and diabetes care [ 48 ]. Although participants were experienced in terms of computer use, and the majority (42/73, 58%) owned a smartphone or laptop computer as demonstrated by the survey, it seemed from the semistructured interviews that participants did not embrace technology fully in daily life, as illustrated by some of the interview participants not taking their mobile phone with them while shopping or their preference to write down their shopping list using paper and pencil as well as to write down their favorite recipes in a notebook.…”
Section: Discussionmentioning
confidence: 99%
“…This may need to be considered when the platform is offered to people with chronic health conditions to increase their engagement and motivation to use features for recipes, meal planning, and creating web-based shopping lists. Apart from personalized recipe suggestions, using AI could improve engagement with such platforms and diabetes care [ 48 ]. Although participants were experienced in terms of computer use, and the majority (42/73, 58%) owned a smartphone or laptop computer as demonstrated by the survey, it seemed from the semistructured interviews that participants did not embrace technology fully in daily life, as illustrated by some of the interview participants not taking their mobile phone with them while shopping or their preference to write down their shopping list using paper and pencil as well as to write down their favorite recipes in a notebook.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that involving end users through usability studies in designing AIgenerated applications has been instrumental in ensuring context-based messaging, curbing language limitations and addressing cultural disparities in delivering and engaging health services (Cordova et al, 2015;Shields et al, 2022). Therefore, to address stigma related to mental health, collaborative efforts in the design of interventions are crucial.…”
Section: Current Mental Health Ai Toolsmentioning
confidence: 99%
“…HCD offers a methodology that allows researchers to explore why variation exists in order to create solutions that are integrated within the needs of various stakeholders (40). The iterative nature of HCD enhances usability and avoids unintended consequences by involving intended users throughout the entirety of the design process, gathering feedback to prioritize user needs using qualitative assessments and interviews (41). Beede and Baylor et al, the first human-centered observational study of a deep learning system deployed in a clinical setting, models the benefit of using HCD to evaluate AI systems, as this methodology helps understand end user needs and their environment, demonstrating how contextualizing these factors is key to the successful implementation of AI technology and acknowledging how success in a clinical environment cannot just depend on the accuracy of the technology alone (42).…”
Section: Human-centered Designmentioning
confidence: 99%